Anthracene‐Attached Persistent Tricyclic Aromatic Hydrocarbon Radicals. Issue 10 (28th January 2019) - Nishiuchi, Tomohiko; Ito, Ryuoh; Takada, Aya; Yasuda, Yuri; Nagata, Takaya; Stratmann, Erik; Kubo, Takashi
Abstract: Anthracene‐attached tricyclic aromatic hydrocarbon radicals having different central polygons, Ant‐5, Ant‐6, andAnt‐7, were synthesized to evaluate the role of an anthracene substituent group in the stability and reactivity of tricyclic aromatic hydrocarbon radicals. The bulky anthryl group effectively protects a carbon atom with high spin density, resulting in high persistence of the radicals. On the other hand, the combination of the anthryl group and the tricyclic aromatic scaffold makes the molecular structure drastically change from a twisted form to a folded form and an unpaired electron moves into the anthryl moiety, eventually affording a tail‐to‐tail σ‐dimer. Abstract : Cool trike, man ! Anthracene‐attached tricyclic aromatic hydrocarbon radicals having different central polygons were synthesized to evaluate the role of an anthracene substituent group in the stability and reactivity of tricyclic aromatic hydrocarbon radicals.